LEARNING OBSTACLES OF IMPLEMENTATION THEMATIC LEARNING IN MATHEMATICS SUBJECTS ELEMENTARY SCHOOL - Sabrina Azzahro; Lailatun Nurul Maulidah; Firna Nahwa Firdausi; Agus Mukti Wibowo; Luthfiya Fathi Pusposari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify, classify, and analyze the factors in the implementation of thematic learning in mathematics subject elementary schools, and formulate recommendations to improve the quality of implementation thematic learning. The research method uses a qualitative approach with a Systematic Literature Review (SLR) study based on the PRISMA guidelines. The process of PRISMA guidelines is identifying, assessing, and synthesizing the results of previous research in a transparent and structured manner. Literature searches are conducted through reputable academic databases with a publication range of 2021–2025 to obtain relevant and up-to-date sources. The results of the analysis showed there are many learning obstacles in mathematics subject elementary school, especially in the epistemological aspect. In the epistemological aspect are caused by less contextual and varied learning approaches, limited use of visual and concrete media, and weak teachers' ability to identify students' conceptual difficulties from the beginning of learning. Contextual approaches and constructivistic learning models are important to be applied to construc students' knowledge.